Two species of metallic Microlepidoptera, one new species of Adela Latreille, [1796] (Adeloidea, Adelidae) and one unrecorded species of Coleophora Hübner, 1822 (Gelechioidea, Coleophoridae), from Korea - Koo, Jun-Mo; Cho, Soowon (Zootaxa, 2022)
One new species of Adela Latreille, [1796], A. palella Koo & Cho, sp. nov., belonging to Adelidae is described from Korea, and one species of Coleophora Hübner, 1822, C. fuscocuprella Herrich-Schäffer, 1855, belonging to Coleophoridae is reported for the first time. Diagnostic characters and descriptions are provided along with close-up photographs of notable features of adults.